Contending with contradictions - Kuo, M; Mercy A. Kuo (1999)
﻿ This doctoral thesis examines the objectives, consequences, and significance of the People's Republic of China's (PRC) policy towards Soviet Eastern Europe with special reference to Poland from 1953 to 1960. The most significant finding of this thesis is the confirmation of the close collaboration between the Chinese and Poles in the events surrounding the Polish October in 1956. This study argues that the Chinese Communist leadership played a decisive role in preventing Soviet military action in Warsaw during those few critical days in October, 1956. In successfully defusing the tension between Moscow and Warsaw, the Chinese reached a parity of prestige in which the PRC could duly consider itself equal with the Soviet Union. With the restoration of its "rightful" place in the postwar world order as the ultimate aim of the Chinese revolution, the PRC forged relations with the Soviet bloc holding the view that equality with the Soviet Union was a crucial prerequisite in recovering its global position. The PRC's Soviet East Europe policy, namely in its relations with Poland, paved the PRC's road toward reaching equality with the Soviet Union, but at the same time exposed the contradictory nature of bloc unity, the weak foundations of Soviet authority, and the deepseated belief of the Chinese leadership in the PRC's sovereign position as the centre of the world Communist revolution. Thus, contending contradictions in intra-party relations between the Chinese Communist Party (CCP), the Polish United Workers' Party (PUWP), and the Communist Party of the Soviet Union (CPSU) formed the crux of the intra-bloc imbroglio which threatened Soviet authority in the bloc and led to the Sino-Soviet split in 1960.